Novel 4,4 '-{(diphenylmethylene) bis(4,1-phenylene)bis(oxy)}-bridged ball-type phthalocyanines: Electrochemical, electrocatalytic oxygen reducing and heavy metals ions sensing properties - (:unkn) unknown (WORLD SCI PUBL CO INC, 2016)
Novel 4,4'-{(diphenylmethylene)bis(4,1-phenylene) bis(oxy)} bridged ball-type metal-free, zinc(II), cobalt(II) and iron(II) ball-type metallophthalocyanines were achieved by the reaction of the bisphthalonitrile derivative in 2-dimetylaminoethanol. The isolation of the metal-free and metallophthalocyanines were carried out by both planar and column chromatography and also by hot soxhalet extraction. Their structures have been characterized by infrared, ultraviolet-visible, H-1 nuclear magnetic resonance and matrix assisted laser desorption/ionization mass spectroscopies. The redox characters of the ball-type metallophthalocyanines have been investigated by cyclic voltammetry, square wave voltammetry, controlled potential coulometry and spectroelectrochemistry in nonaqueous media. The investigation suggested that the ball-type complexes form ring-based and/or metal-based mixed-valence species as a result of the remarkable interaction between the two Pc rings and/or metal centers. Furthermore, these species were found to be stable as evidenced by the splitting of the relevant redox processes. The electrocatalytic oxygen reducing performances of the dinuclear ball-type complexes were also studied. The compound involving Fe(II) centers at the phthalocyanine cores displayed higher catalytic performance towards oxygen reduction than those of other ones. By using these compounds as sensing materials, a flow type quartz crystal microbalance sensor was developed for the detection of small concentrations of heavy metal ions. A cadmium ion sensitivity of 2.85 x 10(4) Hz/mg. L-1 was observed with ball-type iron(II) phthalocyanine coated quartz crystal microbalance sensor. Detection of other metal ions including Fe2+, Zn2+, Ag2+ and Sn2+ were also performed. The results indicated that 1-4 functionalized quartz crystal microbalance sensors can be used for the detection of heavy metal ions in aqueous solution. Partition coefficients obtained from the linear response regimes of the calibration curves are in the 8.6 x 10(4)-5.4 x 10(5) range. Results show that the minor structural difference between metal free and metallophthalocyanine poses significant impact on metal ion partitioning.
Keywords: phthalocyanines; ball-type; electrochemistry; electrochromaticity; oxygen reduction; quartz crystal microbalance sensors; heavy metal ions; REDUCTION; WATER; PERFORMANCE; CATALYSTS; ZINC(II); OFET; LEAD